Southern Hemisphere atmospheric circulation response to the El Chichon and Pinatubo eruptions in coupled climate models - Karpechko, A; Gillett, N; Dall'Amico, M; Gray, L (2010)
We study the response of the Southern Hemisphere circulation to the 1982 eruption of El Chichón and 1991 eruption of Pinatubo volcanoes in a suite of up-to-date coupled climate models. We find a significant response in austral spring and autumn in the years following the eruptions, which consists of a stronger stratospheric polar vortex and lowered sea-level pressure over the Antarctic, both consistent with the positive phase of the Southern Annular Mode. The seasonality of the response may be explained in terms of zonal flow-planetary wave interactions. This dynamical response is inconsistent with the observational reanalyses in the polar stratosphere in spring, but not in the troposphere where the internal variability is large compared to the magnitude of the response. © 2010 Royal Meteorological Society.